Effects of a Multispecies Probiotic Mixture on Glycemic Control and Inflammatory Status in Women with Gestational Diabetes: A Randomized Controlled Clinical Trial - Sadegh Jafarnejad; Sadaf Saremi; Farzan Jafarnejad; Arman Arab (Journal of Nutrition and Metabolism)
Objective. This trial aims to examine the effects of a Probiotic Mixture (VSL#3) on glycemic status and inflammatory markers, in women with GDM. Materials and Methods. Over a period of 8 weeks, 82 women with gestational diabetes were randomly assigned to either an intervention group (n=41) which were given VSL#3 capsule or to a control group which were given placebo capsule (n=41). Fasting plasma glucose, homeostatic model assessment of insulin resistance, glycosylated hemoglobin, high-sensitivity C-reactive protein, tumor necrosis factor-α, interleukin-6, Interferon gamma, and interleukin-10 were measured before and after the intervention. Results. After 8 wk of supplementation FPG, HbA1c, HOMA-IR, and insulin levels remained unchanged in the probiotic and placebo groups. The comparison between the two groups showed no significant differences with FPG and HbA1c, but there were significant differences in insulin levels and HOMA-IR (16.6±5.9; 3.7±1.5, resp.). Unlike the levels of IFN-g (19.21±16.6), there was a significant decrease in levels of IL-6 (3.81±0.7), TNF-α (3.10±1.1), and hs-CRP (4927.4±924.6). No significant increase was observed in IL-10 (3.11±5.7) in the intervention group as compared with the control group. Conclusions. In women with GDM, supplementation with probiotics (VSL#3) may help to modulate some inflammatory markers and may have benefits on glycemic control.